Effects of Zn-EDTA on the health and welfare of the African catfish, Clarias gariepinus (Burchell, 1822), in a recirculating aquaculture system - Hildebrand, Marc-Christopher; Rebl, Alexander; Goldammer, Tom; Palm, Harry Wilhelm; Baßmann, Björn (Frontiers in Aquaculture, 2024)
As nutrient-rich water in aquaponic systems cannot supply the growing plants with all the required trace elements, additional supplementation with specific fertilizers is used to cover this deficit. While chelated fertilizers such as Zn-EDTA are becoming more popular in this context for improving plant growth in aquaponic systems, little is known about their effects on fish. During two experiments, a total of 576 individuals of catfish fry (0.19 g) and fingerlings (220.01 g) of African catfish (Clarias gariepinus, Burchell 1822) were kept separately for 32 days under experimental aquarium conditions. The fry was exposed to 0.125 mg/L and 0.5 mg/L, whether the fingerlings were exposed to 0.5 mg/L and 2.0 mg/L ethylenediaminetetraacetic acid-zinc disodium complex (Zn-EDTA) in a plantless aquaponic system, respectively. The third treatment group consisted of a control group without Zn-EDTA. Growth, mortality, ethological indicators were assessed for all growth stages, while leukocyte distribution and histopathological changes were determined for the fingerlings additionally. As the feed intake in the experiment was limited, the investigations were focused on the effects of Zn-EDTA and not on the growth process of a respective fish growth stage. While growth, mortality, and behavior were not significantly different in both growing stages, the number of mature neutrophils changed significantly in all fingerling treatments. Zn was not detected inside the histological investigated organs at the tested concentrations by the applied staining method. Instead, we found morphological alterations of the gill epithelium on the secondary lamellae. Quantitative multiplex PCR was used to simultaneously evaluate the expression of 17 genes related to Zn metabolism and stress physiology in the head kidney samples. The transcript concentrations of several selected genes changed by up to 70-fold. Due to high individual variances, only the copy numbers of the KMT2A (lysine-specific methyltransferase 2a) gene were significantly different across the treatment groups and sampling points. However, the present results indicate that the addition of Zn-EDTA at the tested concentrations can be considered relatively benign for the health and welfare of C. gariepinus, as no toxic effects of Zn-EDTA were observed in moderately hard to hard water.